1970
DOI: 10.1113/jphysiol.1970.sp009283
|View full text |Cite
|
Sign up to set email alerts
|

Inotropic changes in the left ventricle: the effect of changes in heart rate, aortic pressure and end‐diastolic pressure

Abstract: SUMMARY1. Under conditions where heart rate, mean aortic pressure and enddiastolic pressure in the left ventricle are held constant, the intravenous infusion of isoprenaline is accompanied by large changes in dP/dt max in the left ventricle.2. Under similar conditions, during stepwise increments in the rate of infusion of isoprenaline the changes in dP/dt max (measured at a constant paced heart rate) were proportional to changes in the free (intrinsic) heart rate. It is concluded that dP/dt max is a quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
2
1

Year Published

1971
1971
2015
2015

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(89 citation statements)
references
References 34 publications
4
82
2
1
Order By: Relevance
“…Before discussing the results it is important to consider problems associated with the measurement of direct effects of compounds on the intact heart. Firstly, quantitative measurements of the inotropic effects of compounds on the heart are technically difficult and of doubtful reliability when obtained in the presence of the large changes in heart rate and blood pressure which may be caused by doses of isoprenaline and noradrenaline (Furnival et al, 1970;Mason, Braunwald, Covell, Sonnenblick & Ross, 1971). However, previous experiments in carefully controlled preparations have shown that the same relative changes in force and rate are brought about by many compounds which act on the heart through the P-adrenoceptor (Furnival, Linden & Snow, 1971: Harry, Kappagoda, Linden & Snow, 1973Robie, Nutter, Moody& McNay, 1974;Bolter & Ledsome, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Before discussing the results it is important to consider problems associated with the measurement of direct effects of compounds on the intact heart. Firstly, quantitative measurements of the inotropic effects of compounds on the heart are technically difficult and of doubtful reliability when obtained in the presence of the large changes in heart rate and blood pressure which may be caused by doses of isoprenaline and noradrenaline (Furnival et al, 1970;Mason, Braunwald, Covell, Sonnenblick & Ross, 1971). However, previous experiments in carefully controlled preparations have shown that the same relative changes in force and rate are brought about by many compounds which act on the heart through the P-adrenoceptor (Furnival, Linden & Snow, 1971: Harry, Kappagoda, Linden & Snow, 1973Robie, Nutter, Moody& McNay, 1974;Bolter & Ledsome, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The maximum rate of rise of pressure in the left ventricle of the heart, (dP/dt max) measured at a constant heart rate and mean systemic arterial pressure during each series of infusions, was used as an index of inotropic changes (Furnival, Linden & Snow, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Benefit was demonstrated by an increase in RV dP/dt max , a well-validated index of ventricular systolic performance. 11,12 We selected this as our primary RV outcome because it can be measured independently of ventricular geometry and is insensitive to changes in afterload. Although dP/dt max is affected by alterations in preload, there is no reason to believe that the pacing intervention altered preload acutely, particularly because heart rate was held constant.…”
Section: Baseline Characteristics and Hemodynamic Data Of Study Subjectsmentioning
confidence: 99%